The Impact of Residence Design on Freshman Outcomes: Dormitories Versus Suite-Style Residences - Rodger, Susan C.; Johnson, Andrew M. (Canadian Journal of Higher Education, 2005)
This study was designed to measure affective, behavioural, and cognitive variables in a sample of 3159 first-year students, and to compare these variables by the type of residence building in which the student lived. Students living in suite-style buildings reported a greater sense of belonging, and higher activity levels than students living in dormitory- style buildings. Furthermore, sense of belonging was predicted by high extraversion and low conscientiousness. This suggests that introverted, conscientious students living in traditional dormitory-style buildings may be most at-risk of feeling “out-of-place” in residence.